OP0152-PC Knowledge and Confidence of Practice Nurses in the Management of Osteoarthritis (OA): Pre- and Post-Evaluation of an OA Self-Management Training Programme. (23rd January 2014) - Healey, E. L.; Ryan, S.; McHugh, G. A.; Main, C. J.; Porcheret, M.; Ong, B. N.; Pushpa-Rajah, A.; Dziedzic, K. S.
Abstract : Background: In the United Kingdom (UK), practice nurses do not routinely consult with individuals with OA as most OA care is provided by general practitioners. However, evidence suggests that practice nurses are most likely to provide self-management support for patients with chronic disease in primary care and may be best placed to offer the core treatments recommended in the NICE OA guidelines (2008). Objectives: To i) identify the knowledge and confidence of practice nurses in providing self-management support for patients with OA and ii) examine the impact of an OA self-management training programme designed for practice nurses on knowledge and confidence. Methods: Practice nurses (n = 25) from 8 general practices involved in the MOSAICS trial were invited to complete a questionnaire to determine their knowledge and confidence regarding the management of OA using a 5-point Likert scale (higher scores = greater knowledge/confidence) and the Practitioner Self-Confidence scale (score range 4-20, ≥7 = low confidence). Nurses (n = 9) from the practices randomised to deliver the trial intervention then attended a 4 day training programme designed to enable delivery of the core NICE recommendations (information and advice, exercise/physical activity and weight management) using a patient-centred approach, a specially developed OA guidebook and goal setting, to enable self-management. Everyone that attended the training was asked to complete a post-training questionnaire. Results: Of those invited to participate, 21 (84%) nurses completed the initial questionnaire. All nurses were female, average years qualified was 25.8 years (sd 10.8), 9.5% were further qualified as nurse practitioners and some had experience or training in musculoskeletal medicine (23.8%) or Orthopaedics / Rheumatology (33.3%). In terms of knowledge, only 4.8% scored 4 and above when asked how much they had heard or read about the NICE OA guidelines. All nurses reported very low confidence (16.1 sd 3.0) regarding the decisions needed when caring for patients with chronic joint problems, with 67% reporting no confidence in examining peripheral joints. Of the 9 nurses that undertook the training, 8 (88.8%) completed the post-training questionnaire. Training increased knowledge of OA with all nurses scoring 4 and above when asked how much they had heard or read about the NICE OA guidelines. Confidence also improved significantly in those that were trained with scores improving by 8.6 points on average (p<0.001). Similarly, there was a large shift post-training in the percentage of nurses feeling OA management was part of their role (4.7% to 62.5% scoring 4 or above). Conclusions: NICE recommend that healthcare professionals should support patients with OA to self-manage their condition. The results of this study show a significant gap between what is recommended and what nurses feel they can currently provide in terms of OA management. The development of a practice nurse training prpgramme goes some way to develop a system in primary care for delivering the core recommendations by NICE. Evaluation of the training suggests that it enables practice nurses to feel more knowledgeable and confident in supporting patients to manage their OA more effectively. Disclosure of Interest: None Declared